2007
DOI: 10.1098/rspb.2007.0690
|View full text |Cite
|
Sign up to set email alerts
|

Energetic costs of parasitism in the Cape ground squirrelXerus inauris

Abstract: Parasites have been suggested to influence many aspects of host behaviour. Some of these effects may be mediated via their impact on host energy budgets. This impact may include effects on both energy intake and absorption as well as components of expenditure, including resting metabolic rate (RMR) and activity (e.g. grooming). Despite their potential importance, the energy costs of parasitism have seldom been directly quantified in a field setting. Here we pharmacologically treated female Cape ground squirrel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 86 publications
0
67
0
Order By: Relevance
“…v www.esajournals.org There is growing evidence that ectoparasites can have significant negative impacts on the physiology of individual hosts, and the vital rates of host populations (Hawlena et al 2006a, Hawlena et al 2006b, Devevey et al 2008, Devevey and Christe 2009, Pfäffle et al 2009, Kam et al 2010. Therefore, it is conceivable that lowered ectoparasite loads in burned forest contribute to high post-fire deer mouse abundance, e.g., through effects on body condition (Hawlena et al 2006a, Devevey et al 2008, Devevey and Christe 2009 or feeding behavior (Scantlebury et al 2007, Raveh et al 2011), which in turn influences reproductive output of deer mice. Intriguingly, Raveh et al (2011) showed that flea-infested rodents were less vigilant and v www.esajournals.org had higher giving-up densities (i.e., tended to quit foraging at higher densities of food remaining in the patch).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…v www.esajournals.org There is growing evidence that ectoparasites can have significant negative impacts on the physiology of individual hosts, and the vital rates of host populations (Hawlena et al 2006a, Hawlena et al 2006b, Devevey et al 2008, Devevey and Christe 2009, Pfäffle et al 2009, Kam et al 2010. Therefore, it is conceivable that lowered ectoparasite loads in burned forest contribute to high post-fire deer mouse abundance, e.g., through effects on body condition (Hawlena et al 2006a, Devevey et al 2008, Devevey and Christe 2009 or feeding behavior (Scantlebury et al 2007, Raveh et al 2011), which in turn influences reproductive output of deer mice. Intriguingly, Raveh et al (2011) showed that flea-infested rodents were less vigilant and v www.esajournals.org had higher giving-up densities (i.e., tended to quit foraging at higher densities of food remaining in the patch).…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory studies, fleas were found to affect body condition, growth rate, life span, and energy expenditure of their hosts (e.g., Hawlena et al 2006a, Devevey et al 2008, Devevey and Christe 2009. In free-living animals, ectoparasites influenced host energy budgets (Giorgi et al 2001, Nilsson 2003, Kam et al 2010, litter size (Neuhaus 2003), foraging and vigilance patterns (Scantlebury et al 2007, Raveh et al 2011, and juvenile survival (Hawlena et al 2006b). Such effects could translate into effects on host population abundance, but evidence for such impacts is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In November 2008, animals from the experimental group were injected subcutaneously with Ivomec (Merck, 0.2 lg/g body mass), an anti-nematode drug widely used in rodent studies (e.g., Scantlebury et al 2007), and the control group was injected with propylene glycol, an Ivomec medium. The injections were administered within 24-72 h after trapping.…”
Section: Field Experiments and Handling Of Animalsmentioning
confidence: 99%
“…[22,[65][66][67][68]), there is increasing evidence from studies that show few or no effects (rodents: [55][56]69], bats: [24,70], birds: [71,72]). In female Columbian ground squirrels, contradictory results for adult females and their offspring were obtained for populations in the same geographical area, though during different times (this study versus [27]).…”
Section: Discussionmentioning
confidence: 99%